Morbidity Pattern and Health Seeking Behavior of Elderly People in Surnaya Rural Municipality, Baitadi, Nepa - Pant, Gobind Prasad; Bist, Amrit; Mishra, Durga Khadka; Pandey, Anjila; Sanjel, Seshananda (Journal of Karnali Academy of Health Sciences, 2023)
Background: The number of older persons in the world has increased substantially in recent years and is projected to accelerate in the coming decades. With an increase in the proportion of the aged population, the elderly with ailments is also on the rise. The aged population has special health problems that are different from those of adults or young. This study aims to assess the morbidity patterns and health-seeking behavior of elderly people. Methods: A community-based, cross-sectional study was conducted among 197 elderly people in Surnaya Rural Municipality, Baitadi. Data was collected through face-to-face interview using a pre-tested structured questionnaire. Ethical approval was received, and ethical issues were addressed. Data were processed using SPSS v.25.0. Descriptive statistics and chi-square test was used. Results: The prevalence of morbidity was 71.6%. Respiratory condition was most reported, followed by digestive, musculoskeletal, and cardiovascular diseases. Further, 17.0% sustained injury. Healthcare seeking by 77.3% and 76.1% had treatment compliance. The morbidity condition was significantly associated with economic status (p=0.041), spiritual activity (p=0.032), and difficulty falling asleep (p=0.003). Distance to reach the nearest health facility (p=0.022) and presence of chronic health problems (p<0.001) was significantly associated with healthcare-seeking behavior of the elderly. Conclusion: The high prevalence of multiple morbidities in elderly was reported, among which the respiratory condition was leading. Still, large numbers of elderly do not seek healthcare and have low treatment compliance. Elderly-friendly health services, extension of health insurance, and health screening services are recommended to enhance health-seeking behavior of the elderly.